Photo Response of Locally Isolated Methicillin-Resistant Staphylococcus aureus to Q-switched Nd:YAG Laser In Vitro Study - Rassam, Yasemin Z. (Iraqi Journal of Laser, 2010)
This prospective study investigates the prevalence of methicillin-resistant S.aureus (MRSA) in burn unit of Al-Kindy Iraqi hospital, their susceptibility to antibiotics and bactericidal effect of near infrared light from high powered 1064nm Nd: YAG laser and green light 532nm from SHG Nd: YAG laser using various energy densities on these bacteria. Twenty four clinical isolates of S.aureus out of sixty four examined patients with sever burn ulcers.MRSA was associated with 50% of S.aureus infections .Results of antimicrobial susceptibility revealed that MRSA were multidrug resistant. After laser treatment of non MRSA with Nd:YAG with wavelength of 1.064nm, 4mm beam diameter, energy density of 0.636 kh/cm2 and 180sec exposure time, the diameter of inhibition zone increased for almost of the used antibiotics beside some isolates became sensitive or intermediate except for penicillin (G). For MRSA isolates no observable change in the sensitivity against the antibiotics after 180sec irradiation was observed, except for erythromycin and gentamycin which changed from resistant to intermediate, while vancomycin changed from resistant to sensitive. An inhibitory effect of Nd: YAG laser on MRSA was noticed at all energy densities.Simillarly SHG Nd: YAG laser with chosen energy densities was inhibitory for MRSA .A noticeable decrease in MRSA growth corresponding to 92% was obtained by using SHG Nd: YAG with 0.955J/cm2 energy density, with 3HZ repetition rate and 1260 pulses. Our results demonstrated that methicillin resistant S.aureus can be successfully killed by Q-switched Nd: YAG laser. This effectiveness of Q-switched Nd: YAG in vitro suggests it would be effective in human cases of MRSA infections, and particularly in patients with skin burn infections.